Economic analysis of wet waste-to-energy resources in the United States. (1st June 2019) - Badgett, Alex; Newes, Emily; Milbrandt, Anelia
Abstract: Waste-to-energy (WTE) technologies provide opportunities to use waste materials beneficially in producing power, transportation fuels, and chemicals. Using a suite of economic models, this study estimates prices of four WTE resources: food waste; fats, oils, and greases (FOG); animal manure; and sewage sludge. Some of these materials are commoditized (e.g. FOG) thus their price is determined by market demand. For the materials regarded as waste, the study relates price to the avoided cost of disposal through waste management alternatives such as landfilling. This study finds that significant amounts of these feedstocks could be available at negative prices, meaning that a potential bioenergy facility could receive these materials for free or be paid to accept them in some locations. It is estimated that about 61% of sewage sludge, 27% of manure, and 7% of food waste may be available at negative prices. These negative price feedstocks are not uniformly distributed and are most likely to occur in areas with organic waste disposal bans, high population densities, and high landfill tipping fees. This study intends to open an initial discussion into how stakeholders view and value these materials, and how this view is evolving as their potential as WTE feedstocks is realized. Highlights: The first study to analyze spatial variance in wet waste-to-energy feedstock prices. Feedstocks can be viewed as commodities or wastes depending on location and markets. If a resource has been commoditized (e.g. FOG), its price is determined by market demand. If treated as a waste, feedstock price is driven by the cost of its disposal. Negative waste feedstock prices are driven by disposal costs and organic waste bans.